Measurement of the semileptonic CP asymmetry in B0-B0 mixing - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physical review letters, 2015)
The semileptonic CP asymmetry in B0-¯B0 mixing, adsl, is measured in proton-proton collision data, corresponding to an integrated luminosity of 3.0 fb−1, recorded by the LHCb experiment. Semileptonic B0 decays are reconstructed in the inclusive final states D−μ+ and D*−μ+, where the D− meson decays into the K+π−π− final state and the D*− meson into the ¯D0(→K+π−)π− final state. The asymmetry between the numbers of D(*)−μ+ and D(*)+μ− decays is measured as a function of the decay time of the B0 mesons. The CP asymmetry is measured to be adsl=(−0.02±0.19±0.30)%, where the first uncertainty is statistical and the second systematic. This is the most precise measurement of adsl to date and is consistent with the prediction from the standard model.
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und 679 weitere]
Im Titel steht das zweite "B" mit einem Oberstrich
Im Titel ist "0" jeweils hochgestellt
Gesehen am 20.05.2021